Integration of Nutrient Sensing in Fish Hypothalamus - Soengas, José L. (Frontiers in Neuroscience, 2021)
The knowledge regarding hypothalamic integration of metabolic and endocrine signaling resulting in regulation of food intake is scarce in fish. Available studies pointed to a network in which the activation of the nutrient-sensing (glucose, fatty acid, and amino acid) systems would result in AMP-activated protein kinase (AMPK) inhibition and activation of protein kinase B (Akt) and mechanistic target of rapamycin (mTOR). Changes in these signaling pathways would control phosphorylation of transcription factors cAMP response-element binding protein (CREB), forkhead box01 (FoxO1), and brain homeobox transcription factor (BSX) leading to food intake inhibition through changes in the expression of neuropeptide Y (NPY), agouti-related peptide (AgRP), pro-opio melanocortin (POMC), and cocaine and amphetamine-related transcript (CART). The present mini-review summarizes information on the topic and identifies gaps for future research.